UPAYA MENINGKATKAN OKUPANSI HOTEL SELAMA MASA PANDEMI COVID – 19 DENGAN MEMANFAATKAN ONLINE REVIEW PADA APLIKASI PEGIPEGI DAN TRAVELOKA - Sri Yulianto Fajar Pradapa; Ignatius Hari Santoso (Universitas Merdeka Malang, 2021)
This study aims to measure the benefits of clean and safe information on online hotel reservations. By using a sample of 73 respondents who were analyzed using the partial least square method, this study proves that the higher the level of consumer confidence in the application, the greater the intention to book hotels online. In addition, the better online reviews that are available on the application, the better the intention of booking hotel rooms online as well. Thus, to increase room occupancy, hotels in Yogyakarta cannot rely more on the facts and quality of information conveyed through the Pegipegi and Traveloka applications because potential consumers rely on reviews of previous consumer online results that refer to the application.